Coal desulfurization using gamma and ultraviolet radiation. Issue 11 (3rd June 2017) - Iqbal, Munawar; Ghaffar, Abdul; Nazir, Arif; Yameen, Muhammad; Munir, Bushra; Nisar, Numrah; Bokhari, Tanveer Hussain
ABSTRACT: Combustion of coal produces oxides of sulfur that is harmful for the environment. Present research work was aimed to appraise the desulfurization of coal using high-energy radiations. Gamma radiations (γ-rays) and ultraviolet radiations (UV) were employed for the desulfurization of coal under different media conditions. Coal slurries in these media were treated for different time intervals of UV radiation and γ-rays doses (50, 100, 150 kGy). The maximum sulfur removal was achieved up to 54 and 36% by γ-radiation and UV radiation, respectively, which is due to the more ionizing power of γ-rays treatment. To effectively and efficiently remove sulfur from coal, the use of high-energy radiations is suggested for the desulfurization of coal.